ECONOMIC AND ENVIRONMENTAL CONSIDERATIONS FOR PAVEMENT MANAGEMENT SYSTEMS - Bardeesi, Mohamad Wajdi; Attallah, Youssef (European Scientific Journal, ESJ, 2015)
Sustainability and specifically environmental factors are emerging as prominent issues in engineering decision-making. Environmental parameters are not considered part of current pavement management systems for many road authorities, despite having duties such as pavement construction and maintenance which can greatly affect the environmental impact of a project. This paper demonstrates the feasibility of integrating environmental performance measures into pavement management process. To illustrate these concepts, a sustainable pavement management framework is proposed. Background information is given on life-cycle assessment (LCA). The proposed framework life-cycle and LCA phases are discussed, in addition to the system’s data and data sources. A list describing the data used for environmental calculations is included, Special attention is given to recycled materials and environmental measures. Concluding remarks suggest different contexts for potential applications of the proposed framework, together with network tools that can be used to meet user needs and applications as well as to address feasibility and cost.